FKBP4 Accelerates Malignant Progression of Non-Small-Cell Lung Cancer by Activating the Akt/mTOR Signaling Pathway - Meng, Wen (Anal Cell Pathol (Amst), 2020)
OBJECTIVE: To study the expression, biological function, and mechanism of FKBP4 in non-small-cell lung cancer (NSCLC). METHODS: First of all, the expression of FKBP4 in NSCLC tissues and cell lines was detected by qRT-PCR; then, the effects of FKBP4 on proliferation, apoptosis, migration, and invasion of NSCLC were studied by CCK-8 assays, flow cytometry assays, wound-healing assays, and Transwell assays. After that, tumor xenografts were used to explore the effect of FKBP4 on NSCLC tumor growth in vivo, and the phosphorylation of Akt and mTOR was measured by western blot. RESULTS: FKBP4 was highly expressed in NSCLC tissues and cells, and its expression was closely related to NSCLC tumor size, lymph node metastasis, and patient prognosis. In vitro, FKBP4 can promote NSCLC cell proliferation, migration, and invasion and inhibit NSCLC cell apoptosis. In vivo, FKBP4 can promote NSCLC tumor growth. Furthermore, FKBP4 can promote Akt and mTOR phosphorylation and activate the Akt/mTOR signaling pathway and an mTOR inhibitor can neutralize the functions of FKBP4 in NSCLC cells. CONCLUSION: FKBP4 serves as an oncogene to promote malignant processes in NSCLC, and it has the potential to be used as a biological marker and therapeutic target for NSCLC.